Menumbuhkan Minat Wirausaha Melalui Praktik Ibadah Hukum Islam: Menumbuhkan Minat Wirausaha Melalui Praktik Ibadah Hukum Islam - Nurul Afifah Afifah (el-Bait: Jurnal Hukum Keluarga Islam, 2023)
Entrepreneurship is an important part of worship, so that the path taken should also be in accordance with Islamic teachings themselves. Islam considers all of this important so that humans can more easily carry out other forms of worship such as providing for families, sponsoring orphans, paying zakat and so on. Therefore, aspiring to be rich and working hard as its actualization is included in the realm of worship. Meanwhile, the fact that not many Muslims are economically sovereign is often identified as a result of their entrepreneurial activities not yet fully adopting the principles of Worship in their entrepreneurial activities.